Digital recording and documentation of endoscopic procedures: physicians' practice and perspectives - Maya Peled-Raz; Nadav Willner; Dan Shteinberg; Keren Or-Chen; Tova Rainis (BMC, 2019)
Abstract Background In recent years, it has become increasingly prevalent internationally to record and archive digital recordings of endoscopic procedures. This emerging documentation tool raises weighty educational, ethical and legal issues - which are viewed as both deterrents and incentives to its adoption. We conducted a survey study aimed at evaluating the use of DRD in endoscopic procedures, to examine physicians' support of this practice and to map the considerations weighed by physicians when deciding whether or not to support a more extensive use of DRD. Methods Israeli physicians from specialties that employ endoscopic technics were surveyed anonymously for demographic background, existence and use of recording equipment, existence of institutional guidelines regarding DRD, and self-ranking (on a scale from 1 to 7) of personal attitudes regarding DRD. Results 322 physicians were surveyed. 84% reported performing routine endoscopic procedures, 78% had the required equipment for digital recording, and 64% of them stated that they never or only rarely actually recorded the procedure. General surgeons had the second highest rate of DRD equipment (96.5%) but the lowest rates of DRD practice (17.5%). The average ranking of support of DRD by all participants was 5.07 ± 1.9, indicating a moderately high level of support. Significant positive correlation exists between actual DRD rates and average support of DRD (p < 0.001). Based on mediation models, for all specialties and with no exceptions, having routine recording guidelines and positive support of DRD were found to increase the probability of actual recording. Being a surgeon or an urologist negatively correlated with support of DRD, and decreased actual recording rates. The argument "Recording might cause more lawsuits" was ranked significantly higher than all other arguments against DRD (p < 0.001), and "Recording could aid teaching of interns" was ranked higher than all other arguments in favor of DRD (p < 0.001). Conclusions While DRD facilities and equipment are fairly widespread in Israel, the actual recording rate is generally low and varies among specialties. Having institutional guidelines requiring routine recording and a positive personal support of DRD correlated with actual DRD rates, with general surgeons being markedly less supportive of DRD and having the lowest actual recording rates. Physicians in all specialties were very much concerned about DRD's potential to enhance lawsuits, and this greatly influenced their use of DRD. These findings should be addressed by educational efforts, centering on professionals from reluctant specialties, as well as by the issuing of both professional and institutional guidelines endorsing DRD as well as requiring it where applicable.